2014
DOI: 10.1111/jam.12714
|View full text |Cite
|
Sign up to set email alerts
|

Carpoglyphus lactis(Acari: Astigmata) from various dried fruits differed in associated micro-organisms

Abstract: The study describes the adaptation of C. lactis to feeding on dried fruits including the interaction with micro-organisms. We also identified potentially pathogenic bacteria carried by the mites to dried fruits for human consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 59 publications
4
16
0
Order By: Relevance
“…Furthermore, whether feather mites select among available food resources (fungal preferences have been found in free‐living fungivorous Astigmata, Hubert et al, ; Hubert, Jarosık, Mourek, Kubatova, & Zdarkova, ) or do not need to rely on bacterial symbionts requires further experimental study. Lastly, a hypothesis of an “external‐rumen” mode of feeding, in which mites ingest predigested food (by bacteria), has been also supported in free‐living astigmatan mites (Hubert et al., , ) and would be also compatible with our results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, whether feather mites select among available food resources (fungal preferences have been found in free‐living fungivorous Astigmata, Hubert et al, ; Hubert, Jarosık, Mourek, Kubatova, & Zdarkova, ) or do not need to rely on bacterial symbionts requires further experimental study. Lastly, a hypothesis of an “external‐rumen” mode of feeding, in which mites ingest predigested food (by bacteria), has been also supported in free‐living astigmatan mites (Hubert et al., , ) and would be also compatible with our results.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, many other species of sarcoptiform mites, including many free-living Astigmata, are functionally defined as fungivore-microbivore-detritivores (e.g., Pyroglyphidae and most oribatid mites, Walter & Proctor 2013a,b), and our results also support this classification for feather mites. In fact, our results are in large agreement with previous studies on microbes found in other mite species (Chaisiri, | 211 evidence has been found for the utilization of bacteria as a food source in free-living astigmatan species (Erban & Hubert, 2008, 2010Hubert, Nesvorna, Kopeck y, S agov a-Mare ckov a, & Poltronieri, 2014;Hubert et al, 2016). In these studies, microbiomes composed of highly diverse taxa in low abundance have been interpreted as evidence for microbivory.…”
Section: B U L W E R I a B U L W E R I I C A L O N E C T R I S D I O supporting
confidence: 93%
“…The differences in bacterial communities confirm the previous results: there is clear variation in bacterial communities among different populations of mites, and this variation may be due to environmental factors such as differences in the diet, micro-habitat or simply the geographic sources, as shown previously for Rhizoglyphus robini ( Zindel et al, 2013 ) and Carpoglpyhus lactis ( Hubert et al, 2015 ). The bacterial community of T. putrescentiae was formed mainly by symbiotic or parasitic bacteria, and contained previously identified bacteria including Bartonella -like, Cardinium ( Kopecky et al, 2013 , 2014b ), and Wolbachia ( Brown and Lloyd, 2015 ).…”
Section: Discussionsupporting
confidence: 90%
“…1), followed by cloning and sequencing of selected clones for taxonomic assignment Lehane, 1999, 2001;Hoy and Jeyaprakash, 2005;Hubert et al 2012Hubert et al , 2014Tang et al 2013;Murillo et al 2014). 1), followed by cloning and sequencing of selected clones for taxonomic assignment Lehane, 1999, 2001;Hoy and Jeyaprakash, 2005;Hubert et al 2012Hubert et al , 2014Tang et al 2013;Murillo et al 2014).…”
Section: Methodological Approaches To the Identification Of Bacteria mentioning
confidence: 99%